Amygdala reactivity during socioemotional processing and cortisol reactivity to a psychosocial stressor. (October 2022) - Roberts, Andrea G.; Peckins, Melissa K.; Gard, Arianna M.; Hein, Tyler C.; Hardi, Felicia A.; Mitchell, Colter; Monk, Christopher S.; Hyde, Luke W.; Lopez-Duran, Nestor L.
Abstract: Threat-related amygdala reactivity and the activation of the Hypothalamic-Pituitary-Adrenal (HPA) axis have been linked to negative psychiatric outcomes. The amygdala and HPA axis have bidirectional connections, suggesting that functional variation in one system may influence the other. However, research on the functional associations between these systems has demonstrated mixed findings, potentially due to small sample sizes and cortisol sampling and data analytic procedures that investigate only pre-post differences in cortisol rather than the specific phases of the cortisol stress response. Further, previous research has primarily utilized samples of adults of mostly European descent, limiting generalizability to those of other ethnoracial identities and ages. Therefore, studies addressing these limitations are needed in order to investigate the functional relations between amygdala reactivity to threat and HPA axis stress responsivity. Using a sample of 159 adolescents from a diverse cohort (75% African American, ages 15–17 years), the present study evaluated associations between amygdala reactivity during socioemotional processing using fMRI and HPA axis reactivity to a socially-evaluative cold pressor task. Greater amygdala activation to fearful and neutral faces was associated with greater cortisol peak values and steeper activation slope. As cortisol peak values and cortisol activation slope capture the intensity of the cortisol stress response, these data suggest that greater activation of the amygdala in response to social distress and ambiguity among adolescents may be related to hyper-reactivity of the HPA axis. Highlights: Greater amygdala activation to fear associated with greater cortisol activation slope. We found coupling of amygdala and HPA axis activation to threat in separate tasks. Our findings are based on a highly diverse sample of adolescents.